A mixed‐methods analysis of patient safety incidents involving opioid substitution treatment with methadone or buprenorphine in community‐based care in England and Wales. (27th April 2020) - Gibson, Russell; MacLeod, Natalie; Donaldson, Liam J.; Williams, Huw; Hibbert, Peter; Parry, Gareth; Bhatt, Jay; Sheikh, Aziz; Carson‐Stevens, Andrew
Abstract : Background and Aims: Opioid substitution treatment is used in many countries as an effective harm minimization strategy. There is a need for more information about patient safety incidents and the resulting harm relating to this treatment. We aimed to characterize patient safety incidents involving opioid substitution treatment with methadone or buprenorphine in community‐based care by: (i) identifying the sources and nature of harm and (ii) describing and interpreting themes to identify priorities to focus future improvement work. Design: Mixed‐methods study examining patient safety incident reports involving opioid substitution treatment with either methadone or buprenorphine in community‐based care. Setting: Data submitted between 2005 and 2015 from the National Reporting and Learning System (NRLS), a national repository of patient safety incident reports from across England and Wales. Participants: A total of 2284 reports were identified involving patients receiving community‐based opioid substitution treatment. Measurements: Incident type, contributory factors, incident outcome and severity of harm. Analysis involved data coding, processing and iterative generation of data summaries using descriptive statistical and thematic analysis. Findings: Most risks of harm from opioid substitution treatment came from failure in one of four processes of care delivery: prescribing opioid substitution ( n  = 151); supervised dispensing ( n  = 248); non‐supervised dispensing ( n  = 318); and monitoring and communication ( n  = 1544). Most incidents resulting in harm involved supervised or non‐supervised dispensing ( n  = 91 of 127, 72%). Staff‐ (e.g. slips during task execution, not following protocols) and organization‐related (e.g. poor working conditions or poor continuity of care between services) contributory factors were identified for more than half of incidents. Conclusions: Risks of harm in delivering opioid substitute treatment in England and Wales appear to arise out of failures in four processes: prescribing opioid substitution, supervised dispensing, non‐supervised dispensing and monitoring and communication.